2023
DOI: 10.3390/ma16020749
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Influence of the Copper Component’s Shape on the Properties of the Friction Material Used in Brakes—Part One, Tribological Properties

Abstract: Brakes play an extremely important role in any vehicle. In today’s automotive industry, friction brakes are most often used, in which the composite material of the brake pad cooperates with a cast iron disc. While little can be modified in the case of discs, in the case of pads, the composition of the material used for its production can have an almost unlimited number of possibilities. Both scientists and manufacturers invent and test new combinations to achieve the desired end result. A similar task was unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Currently, this role is most often played by aramid, and sometimes by carbon or glass fibers. Unfortunately, as described in a previous work (Borawski, 2023), their production is associated with particular hazards for humans and the environment.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Currently, this role is most often played by aramid, and sometimes by carbon or glass fibers. Unfortunately, as described in a previous work (Borawski, 2023), their production is associated with particular hazards for humans and the environment.…”
Section: Introductionmentioning
confidence: 92%
“…In the previous works, it was shown that the shape of the copper could indeed affect the COF. Using fibers instead of round particles and removing aramid increased the coefficient of friction by about 13% (Borawski, 2023). The purpose of this work is to examine how the above change in the reinforcement method affects mechanical properties of the composite friction material.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that in composites, the use of small graphite particles compared to large particles improves the thermal properties of discs. The use of a coppermetal matrix for brake pads shows better tribological properties [8,9]. New materials are also used.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve the desired outcome, manufacturers and scientists have created and experimented with different combinations. Borawski investigate whether copper could replace the materials often utilised as reinforcing materials, given that these materials are often associated unfavourable risks throughout the production process [ 10 ]. To find the abrasive wear rate and the COF, tribological experiments were performed on a number of samples that included copper in the form of both powder and fibres.…”
Section: Introductionmentioning
confidence: 99%